2000
DOI: 10.1038/sj.ejhg.5200402
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variation and genetic heterogeneity in Léri-Weill syndrome

Abstract: Léri-Weill syndrome (LWS) or dyschondrosteosis represents a short stature syndrome characterised by the mesomelic shortening of the forearms and lower legs and by bilateral Madelung deformity of the wrists. Recently, mutations in the pseudoautosomal homeobox gene SHOX have been shown to be causative for this disorder. This gene has previously been described as the short stature gene implicated in Turner syndrome (TS). We studied 32 Léri-Weill patients from 18 different German and Dutch families and present cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
131
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(140 citation statements)
references
References 14 publications
9
131
0
Order By: Relevance
“…1 Haploinsufficient loss of the SHOX gene causes short stature and has been correlated with variable skeletal phenotypes frequently observed in Léri-Weill and Turner syndrome patients (2)(3)(4)(5)(6). SHOX-deficient individuals exhibit a considerable phenotypic heterogeneity ranging from mild, barely detectable skeletal malformations to severe dysplasia adversely affecting the life of these patients (7,8). This phenotypic heterogeneity is clinically well documented but not understood on a molecular level.…”
Section: From the Institute Of Human Genetics Ruprecht-karls-universmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Haploinsufficient loss of the SHOX gene causes short stature and has been correlated with variable skeletal phenotypes frequently observed in Léri-Weill and Turner syndrome patients (2)(3)(4)(5)(6). SHOX-deficient individuals exhibit a considerable phenotypic heterogeneity ranging from mild, barely detectable skeletal malformations to severe dysplasia adversely affecting the life of these patients (7,8). This phenotypic heterogeneity is clinically well documented but not understood on a molecular level.…”
Section: From the Institute Of Human Genetics Ruprecht-karls-universmentioning
confidence: 99%
“…SHOX-deficient individuals exhibit a considerable phenotypic heterogeneity ranging from mild, barely detectable skeletal malformations to severe dysplasia adversely affecting the life of these patients (7,8). This phenotypic heterogeneity is clinically well documented but not understood on a molecular level.…”
mentioning
confidence: 99%
“…LWD is an inherited skeletal dysplasia characterized by disproportionate short stature, mesomelic limb shortening and Madelung deformity of the arm. Later studies have found submicroscopic deletions in the SHOX gene in 34% to 81% of affected families and point mutations in the SHOX gene in 19% to 39% of LWD families studied [38][39][40][41][42][43][44][45][46]. Patients with SHOX haploinsufficiency could benefit from early growth hormone treatment, so early screening of children with unexplained short stature has been suggested [47,48].…”
Section: Par1/par2 and Diseasementioning
confidence: 99%
“…1,2 Depending on the population analyzed, between 60-90% of LWD cases are caused by haploinsufficiency of the short stature homeobox gene (SHOX), which is situated in the pseudoautosomal region of the human sex chromosomes. [3][4][5] SHOX encodes a homeodomain transcription factor and is strongly expressed in developing limb buds and in fetal and prepubertal growth plates, suggesting a role in bone development. In addition to its function underlying the growth and skeletal deficits of LWD and Langer syndrome, 1,2 SHOX haploinsufficiency is also the primary cause of short stature in Turner Syndrome 6 and in about 5-15% of patients diagnosed clinically as having idiopathic short stature.…”
Section: Introductionmentioning
confidence: 99%